Oncological alertness in the practice of a primary care dentist - V. V. Shkarin; Y. A. Makedonova; O. Yu. Afanasyeva; A. V. Poroshin; L. A. Devyatchenko (Эндодонтия Today)
Relevance. Malignant neoplasms are oncological diseases that occur all over the world. Often, the diagnosis is made too late, the onco-alertness of primary care dentists plays a huge role in preventing the development of the disease. Also, timely recognition and treatment of precancerous changes in the oral mucosa is an important aspect of cancer prevention. In most cases, it is not possible to accurately predict the probability of malignancy, however, at a clinical appointment, the most important aspect is to identify both risk factors and initial signs of the development of the pathological process in the absence of complaints from the patient.  Aim. To draw the attention of primary-level dentists to the tactics of patient management from the position of oncological alertness.  Materials and methods. The paper presents the algorithm of the dentist's action at an outpatient appointment, demonstrates the clinical cases of patients. Which were routed according to the presented algorithm.  Results. The prevalence of benign-malignant neoplasms makes it necessary for dentists to know various types of manifestations of pathological conditions. Modern, timely, non-invasive diagnostics, early detection of predictors, referral of patients to specialists of a related profile will prevent the development of complications, including malignancy. Conclusions. The primary care dentist must remember that the chronic prolonged course of the process can cause the invasion of cancer cells into the submucosal layer, into the regional lymph nodes.